Effects of Brain Gym Exercises and Filial Play Therapy on Emotion Management Skills of Students with Specific Learning Disorder - Sosan Kordbacheh; Sahar Safarzadeh; Marjan Alizadeh (Shiraz University of Medical Sciences, 2022)
Background: Students with learning disabilities experience cognitive, emotional, behavioral, and social problems. The present study aimed to investigate the role of brain gym exercises and filial play therapy on students with specific learning disorders (SLD) emotion management skills.Methods: This quasi-experimental study was conducted through a pretest-posttest-follow-up design with a control group. The statistical population included all students with SLD and their mothers in Tehran, Iran within 2020-2021 period. The convenience sampling method was employed to select 45 students with SLD, who were then randomly assigned into two experimental groups and one control group. The participants in the first experimental group received brain gym exercises, whereas those in the second experimental group attended a filial play therapy intervention. The participants in the control group received no intervention. The Children's Emotional Management Scale (CEMS) was used to collect data. The ANCOVA was then adopted for data analysis.Results: The mean±SD of the post-test scores of inhibition, dysregulation, and coping in the brain gym exercises group were 21.73±2.84, 20.00±2.82, and 23.13±3.37, respectively. Moreover, the mean±SD of the post-test scores of inhibition, dysregulation, and coping in the filial play therapy group were 20.53±3.44, 21.53±2.10, and 22.80±3.74, respectively, which were significantly different from the control groups. The results showed that both brain gym exercises and filial play therapy were effective in improving emotion management skills (i.e., inhibition, dysregulation, and coping) in students with SLD (P<0.001). Furthermore, these two interventions had no significant differences regarding their effects on emotion management skills.Conclusions: It can be concluded that brain gym exercises and filial play therapy help improve emotion management skills in students with SLD.